2019
DOI: 10.1101/2019.12.27.889568
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Type I interferons act directly on nociceptors to produce pain sensitization: Implications for viral infection-induced pain

Abstract: ABSTRACTOne of the first signs of viral infection is body-wide aches and pain. While this type of pain usually subsides, at the extreme, viral infections can induce painful neuropathies that can last for decades. Neither of these types of pain sensitization are well understood. A key part of the response to viral infection is production of interferons (IFNs), which then activate their specific receptors (IFNRs) resulting in downstream activation of cellular signaling and a vari… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 66 publications
5
27
1
Order By: Relevance
“…The data are also largely in keeping with the findings of a recent study of single-cell RNAseq analysis of 88 airway specific vagal sensory neurons (Mazzone et al 2020). Previous studies have shown that both type 1 and type 2 IFN receptors are also expressed in sensory neurons in the dorsal root ganglion and play a role in sensitizing nociceptors (Barragan-Iglesias et al 2020). Moreover, these receptors appear to be transported towards the central and peripheral terminals (Neumann et al 1997;Vikman et al 1998;Liu et al 2016).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The data are also largely in keeping with the findings of a recent study of single-cell RNAseq analysis of 88 airway specific vagal sensory neurons (Mazzone et al 2020). Previous studies have shown that both type 1 and type 2 IFN receptors are also expressed in sensory neurons in the dorsal root ganglion and play a role in sensitizing nociceptors (Barragan-Iglesias et al 2020). Moreover, these receptors appear to be transported towards the central and peripheral terminals (Neumann et al 1997;Vikman et al 1998;Liu et al 2016).…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies have shown that both type 1 and type 2 IFN receptors are also expressed in sensory neurons in the dorsal root ganglion and play a role in sensitizing nociceptors (Barragan‐Iglesias et al . 2020). Moreover, these receptors appear to be transported towards the central and peripheral terminals (Neumann et al .…”
Section: Discussionmentioning
confidence: 99%
“… 105 The painful peripheral neuropathies observed in some COVID-19 patients could be associated with interferon-1-induced hyperexcitability of DRG neurons resulting from viral infection. 108 A similar exacerbated immune response may also account for the peripheral vascular inflammatory reactions observed in the multisystem Kawasaki-like syndrome that affects some COVID-19 patients, 109 , 110 particularly children. Dermatological manifestations of COVID-19 such as maculopapular exanthem present in ∼36% of patients 111 could also progress from the DRG neuron to the skin in an anterograde fashion, as schematically shown in the bottom right portion of Figure 2 (red arrow).…”
Section: Alternative Hypothetical Routes That Sars-cov-2 May Follow Tmentioning
confidence: 99%
“…Peripheral neurons are capable of responding to type I IFN signaling, given the robust induction in ISG expression and formation of PML-NBs following treatment with IFNα, and this is supported by a number of previous studies (Yordy et al, 2012, Katzenell and Leib, 2016, Song et al, 2016, Barragan-Iglesias et al, 2020. Importantly, however, peripheral neurons produce little to no type I interferons upon HSV infection (Yordy et al, 2012, Rosato andLeib, 2014), indicating that IFN production arises from other surrounding infected cells.…”
Section: Discussionmentioning
confidence: 66%